Insecticide-treated net utilization and associated factors among pregnant women in Ethiopia: a systematic review and meta-analysis - Bajrond Eshetu; Habtamu Bekele; Adera Debella; Addis Eyeberu; Bikila Balis; Sisay Habte; Kibiru Mardasa; Fenta Wondimneh; Tilahun Teshager; Indeshaw Ketema (Frontiers Media S.A., 2023)
BackgroundMalaria is a major public health problem in many developing countries, particularly in sub-Saharan Africa. The pregnant woman, fetus, and newborn infant are all at risk from malaria during pregnancy. Hence, insecticide-treated bed net (ITN) use is the most effective and advisable method for preventing malaria during pregnancy. Studies on the prevalence of ITN utilization among pregnant women in Ethiopia are inconsistently reported and highly varied. Therefore, this systematic review and meta-analysis aimed to estimate the pooled prevalence of ITN utilization and associated factors among pregnant women in Ethiopia.MethodsA comprehensive search of databases such as PubMed, CINAHL, Web of Science, SCOPUS, Science Direct, Google, and Google Scholar was performed to find studies conducted in Ethiopia. All original observational studies that reported the prevalence of ITN utilization were identified and screened. The Newcastle-Ottawa scale tool was used to assess the quality of the studies. Data were extracted in Microsoft Excel 2010 format and analyzed using STATA Version 14. A random-effect meta-analysis model was utilized to estimate the pooled prevalence of ITN utilization. The statistical heterogeneity was checked using the I2 test and subgroup analysis. The publication bias was assessed using funnel plots and Egger's regression test. The size of the pooled effect of the factors influencing the use of ITNs was estimated using an odds ratio (OR) with a 95% confidence interval (CI), and a P-value <0.05 was considered statistically significant.ResultsTwenty-nine cross-sectional studies with 13,957 study participants were included in this meta-analysis. The overall pooled prevalence of ITN utilization among pregnant women in Ethiopia was 51% (95% CI: 43-60). A statistically significant heterogeneity was observed across studies (I2 = 99.09%; P < 0.001). Being literate [OR = 2.93 (95% CI: 2.14-4.01)], rural residence [OR = 1.76 (95% CI: 1.37-2.26)], and having knowledge of ITN [OR = 4.13 (95% CI: 1.57-10.81)] were factors significantly associated with ITN utilization among pregnant women.ConclusionThe utilization of ITNs among pregnant women was substantially lower than the national target, alarmingly highlighting the need for urgent and effective interventions. Maternal education status, place of residence, and knowledge of ITNs were independent predictors of ITN utilization. Health policymakers and programmers should design and implement the most effective strategies to scale up the utilization of ITNs by pregnant women and reduce malaria-related morbidity during pregnancy.Systematic Review RegistrationCRD42022304432.